Maqāṣid cum-Mubādalah Methodology of KUPI: Centering Women’s Experiences in Islamic Law for Gender-Just Fiqh - Abdul Kodir, Faqiuddin; Nor Ismah; Samia Kotele; Wakhit Hasyim; Fadzila Din (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
The production of fatwā in Indonesia has traditionally been dominated by male scholars and rooted in conventional methodologies that prioritize textual sources, often neglecting the lived experiences of women. This article examines innovative methodology proposed by the Indonesian Congress of Women Ulama (Kongres Ulama Perempuan Indonesia, or KUPI) to develop a gender-just approach to Islamic jurisprudence (fiqh). Drawing on participant observation of KUPI's fatwa-making processes in two events occurring respectively in 2017 and 2022 and literature analysis, this study explores two key questions: (1) To what extent does KUPI’s maqāṣid cum-mubādalah methodology foster gender-just fiqh? (2) How does KUPI apply this methodology, incorporating both women’s experiential perspectives and literal Islamic texts, in issuing its fatwā on child marriage and abortion in cases of rape? The analysis highlights how KUPI’s maqāṣid cum-mubādalah approach challenges traditional jurisprudence, showcasing its transformative potential. KUPI’s framework integrates maqāṣid asy-syarī’ah (the objectives of Islamic law) with mubādalah a perspective emphasizing equality and reciprocity between men and women. Termed maqāṣid cum-mubādalah, this methodology recognizes lived experiences of women as one of the sources to formulate religious opinions, or fatwā, in Islamic legal tradition. This article underscores the importance of integrating women's experiential perspectives into Islamic legal discourse, offering new insights into evolving interpretations of fiqh that prioritize justice and equality.